Untangling the Conundrum of the Panel of Consultants' Utilization in Indonesia - Pratiwi, Tammy Amelia; Qadri, Resi Ariyasa (Policy & Governance Review, 2024)
This interpretivism study utilizes the Oligopticon theory to investigate the underutilization of the Panel of Consultants in Indonesia by identifying the reasons behind its infrequent use and proposing effective solutions. The study employs thematic analysis to process data collected from various sources into thematic codes. In 2018, the Committee for Acceleration of Priority Infrastructure Delivery formed the Panel of Consultants to streamline the consultancy services selection in National Strategic Projects and other priority infrastructures yet was not optimally utilized. The findings indicate that the Panel's underutilization stems primarily from inadequate dissemination, budget constraints, and consultant- related issues. To address these challenges, the study proposes a strategic approach comprising disseminating and expanding knowledge, regular updates and provision of consultant resources, and mandatory usage coupled with centralized budgeting. This study provides regulators with valuable insights into assessing the effectiveness of the Panel of Consultants as a tool for expediting infrastructure development. The findings are crucial for future considerations on its re-establishment. By exploring the Oligopticon theory in the context of public procurement and delving into the method of consultancy selection, the research addresses a significant gap in the literature, offering a unique perspective rarely covered in earlier studies.